Case report: a case of multiple splenic abscesses in a child and literature review - Yang, Yingchun; Liu, Jian; Zheng, Zebing; Tang, Chengyan; Zhu, Daiwei; Xia, Xingrong; Huang, Lu; Du, Qing; Hao, Yongxing; Liu, Yuanmei; Jin, Zhu (Frontiers in Pediatrics, 2023)
Splenic abscesses in children are very rare, and multiple splenic abscesses are rarer. These lesions are difficult to diagnose quickly because of their low incidence and the low specificity of the associated clinical and imaging findings. The treatment of splenic abscesses includes conservative treatment, percutaneous drainage, and splenectomy, but the selection criteria for treatment are still unclear. We present a case of a 13-year-old girl with multiple splenic abscesses. Her blood culture report was negative. We eventually confirmed the diagnosis by enhanced magnetic resonance imaging (MRI). The patient underwent a successful laparoscopic total splenectomy, and her symptoms were resolved thereafter.